Students’ Assessment of Open Distance Learning Programmes and Services in Nigeria: A Comparative Description of Three Selected Distance Learning Institutions - Sunday A. Itasanmi; Mathew T. Oni; Omobola O. Adelore (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2020)
This study reported students' assessment of open and distance learning programmes and services vis-à-vis teaching and learning experience, educational resources, technical support service and infrastructural facilities in ODL institutions in Nigeria. The study adopted a descriptive survey research design and the participants for the study comprised of 719 students randomly drawn from three purposively selected ODL institutions in Nigeria. A semi-structured questionnaire was used as an instrument for the study. Quantitative data generated from the survey were analysed using frequency counts, percentages, and analysis of variance (ANOVA) while the qualitative data was content analysed. Result of the study showed that students enrol in open and distance learning programmes majorly as a result of the flexibility in learning. While students relatively rate their teaching & learning experience, educational resources and available infrastructural facilities in their universities good, they, however, rate technical support services provided in the ODL institutions as being poor. A comparative analysis of the students’ assessment in the three institutions revealed that there exists a statistically significant difference in teaching & learning experiences, available educational resources, technical support services and infrastructural facilities in the institutions. Based on the findiings of the study, some recommendation were made.